Efektivitas Pembelajaran Daring Bahasa Jawa Menggunakan Google Kelas dan Quizizz Pada Siswa SMP Negeri 1 Kayen - Kumalasari, Vania Vania (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2020)
The purpose of this study was to describe the effectiveness of online learning in Javanese using the Google Class and Quizizz applications for students of SMP Negeri 1 Kayen. This research was a classroom action research with 34 students as the subject of research in class VII G SMP Negeri 1 Kayen. This research was conducted in 2 continuous cycles, each cycle of 4 meetings. Each meeting consists of 4 stages of activities, namely planning, implementing, observing, and reflecting. Based on the results of research and discussion, it was concluded that in the pre-cycle, it was found that 53% of students were active in the ineffective category, and 56% of students who achieved completeness were in the incomplete category. In the first cycle data obtained 74% of students who were active with the effective category and 74% of students who achieve completeness with the complete category, while in the second cycle data obtained are 79% active students with the effective category and 77% students who achieve completeness with the complete category. So from pre-cycle and cycle I there was an increase in student activeness as much as 21% and an increase in students who reached 18% completeness, while from cycle I and cycle II there was an increase in student activity by 5% and an increase in students who achieved completeness by 3%. The results showed that learning using Google Class and Quizizz could increase the effectiveness of online learning in Javanese for SMP Negeri 1 Kayen students by 26% from other dimensions and an increase in students achieving 21% completeness from other dimensions.